The Influence of World Gold Prices and Interest Rates on the Stock Price Index with Exchange Rates as a Mediating Variable on the Indonesia Stock Exchange - Farhana Hasmin; Ira Nasriani; Ansar Mustakin; Nurul Muhrisa (BJRM (Bongaya Journal of Research in Management), 2025)
Research was carried out to determine the effect of gold prices and interest rates on the stock price index by using the exchange rate variable as a mediating variable. This relationship was carried out using samples of stock prices, interest rates, stock prices and exchange rates in the last 3 years. Data analysis using SPSS 23.0 software. From the results of the data analysis carried out, the following results were obtained: Gold Prices Have a Significant Negative Influence on the Composite Stock Price Index on the Indonesian Stock Exchange, Interest Rates Have a Significant Negative Influence on the Composite Stock Price Index on the Indonesian Stock Exchange, Exchange Rates Have a Significant Negative Influence on the Stock Price Index Combined on the Indonesian Stock Exchange, the price of gold has no significant negative influence on the exchange rate on the Indonesian Stock Exchange, interest rates have a significant negative influence on the exchange rate on the Indonesian Stock Exchange, the price of gold indirectly has no significant influence on the Composite Stock Price Index through the exchange rate on the Indonesian Stock Exchange , Interest Rates Indirectly Have No Significant Influence on the Composite Stock Price Index Through the Exchange Rate on the Indonesian Stock Exchange.